Pain acceptance and pain-related disability predict healthcare utilization and medication intake in patients wwith non-specific chronic spinal pain - Esteve-Zarazaga, Rosa; López-Martínez, Alicia Eva; Ruiz-Párraga, Gema Teresa; Serrano-Ibáñez, Elena Rocío; Ramírez-Maestre, María del Carmen (MDPI, 2020)
Longitudinal research is needed to determine predictive factors of healthcare utilization and medication intake in people with non-specific spinal pain. This study aims to prospectively examine the predictive value of sex, age, work status, pain intensity, pain acceptance, disability, depression, pain anxiety, and catastrophizing in relation to healthcare utilization and medication intake in people with non-specific spinal pain. Participants were 79 patients with non-specific spinal pain of 6 to 9 months’ duration. They were followed-up at 6 months and 12 months. At enrolment they were administered a battery of questionnaires assessing the predictive variables. Healthcare utilization and medication intake were assessed at follow-ups 1 and 2. At follow-up 1, higher pain acceptance was associated with less healthcare utilization and less medication intake, while male sex was associated with less medication intake. At follow-up 2, higher pain-related disability was associated with higher healthcare use, and pain intensity was associated with higher medication intake. These results suggest that during the early stages of non-specific spinal pain chronification, pain acceptance and the avoidance of pain-related disability—understood as giving up normal activities—can lead to reductions in healthcare utilization and medication intake
Keywords: Prospective study; Medication intake; Healthcare utilization; Disability; Chronic pain; Pain acceptance